The role of artificial intelligence in teaching Turkish to foreigners and chat GPT assessment for writing skills - Uzun, Cemile (IGI Global, 2024)
There are many benefits of adapting artificial intelligence to foreign language teaching. In this study, the adaptation of ChatGPT to teach Turkish to foreigners is discussed. The aim of the study is to evaluate the effect of using ChatGPT against traditional methods in developing writing skills in foreign language teaching. Experimental and control groups were formed to investigate the importance of ChatGPT in teaching Turkish to foreigners. The groups were exposed to A2-B1 level writing activities for six weeks. At the end of the activities, students were given feedback by both ChatGPT and teachers. Which of the feedbacks was more effective was evaluated. It was determined which of the ChatGPT and traditional methods was more effective in developing writing skills. © 2024, IGI Global. All rights reserved.